New Soliton Applications in Earth's Magnetotail Plasma at Critical Densities - Abdelwahed, Hesham G.; Abdelrahman, Mahmoud A. E.; Inc, Mustafa; Sabry, R. (Frontiers in Physics, 2020)
The mathematical new plasma wave solutions are specified in the compose of trigonometric, rational, hyperbolic, periosic and explosive kinds that are realistic for MKP equation. Also, numeral studies for the acquired solutions have been reveals that periodic, shock and explosive new forms may applicable in layer of Earth's magnetotail plasma. The used method is influential and robust in comparison applications in plasma fluids. To depict the propagating soliton profiles in plasma medium, it is needful to solve MKP equation at critical densities. The Riccati-Bernoulli sub-ODE technique has been utilized to introduce some new important and applicable solutions. Number of the these MKP solutions give a leading deed in applied electron acoustics in magnetotail